Beside You in Time : Sense Methods and Queer Sociabilities in the American Nineteenth Century - Freeman, Elizabeth, 1966- (Book collections on Project MUSE., 2019)
Elizabeth Freeman expands bipolitical and queer theory by outlining a temporal view of the long nineteenth century and showing how time became a social and sensory means by which people resisted disciplinary regimes and assembled into groups in ways that created new forms of sociality.